THE The Role of Exercise Physiology in Improving Physical Fitness: A Systematic Literature Review - Habil Tuqya; Wawan Junresti Daya; Tri Bayu Norito; Boy Indrayana; Ilham (Athena: Physical Education and Sports Journal, 2026)
Abstracts: Physical fitness is an important indicator of health and physical performance that enables individuals to perform daily activities efficiently without excessive fatigue. Exercise physiology provides scientific knowledge regarding the body's responses and adaptations to physical activity and training programs. This study aimed to examine the role of exercise physiology in improving physical fitness through a Systematic Literature Review (SLR). Literature was collected from Google Scholar using the Publish or Perish application with the keywords "Sport Physiology" and "Physical Fitness" for publications between 2021 and 2026. A total of 976 articles were initially identified, and after applying inclusion and exclusion criteria based on the PRISMA framework, 10 relevant articles were selected for review. The findings indicate that exercise physiology contributes to improvements in cardiorespiratory endurance, muscular strength, muscular endurance, body composition, energy metabolism, and recovery processes. Regular and structured physical training promotes physiological adaptations that enhance overall fitness and athletic performance. The review concludes that exercise physiology serves as a fundamental scientific basis for designing effective training programs aimed at improving physical fitness and maintaining long-term health.